The Impact of Socialist Feminism on Strengthening Women's Capacity: Case Study on Home Industry Management in Basuhan Village, Eromoko Subdistrict, Wonogiri Regency, Central Java Province - Merina, Bresca; muhaimin; Pramesti, Lisa Aprilia (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Women are often stereotyped as weak and easily oppressed, prompting the rise of feminist movements, including socialist feminism, which views women’s oppression as rooted in both capitalism and patriarchy. This study aims to describe and analyze the impact of socialist feminism on strengthening women's capacity in managing home industries in Basuhan Village, Eromoko District, Wonogiri Regency, Central Java. Using a descriptive qualitative approach, data were collected through observation, interviews, and document analysis. The findings show that socialist feminism has positively influenced women's self-confidence and motivation to improve their economic conditions. Women who receive family support, earn their own income, and are independent of their husbands tend to have higher confidence and drive for change. However, negative impacts were also found, particularly in the quality of family relationships and parenting, which some women still struggle to maintain effectively. Overall, the strengthening of women’s capacity is reflected in key entrepreneurial traits such as task and result orientation, risk-taking, leadership, future planning, creativity, and innovation. The study suggests that working women and home industry owners should maintain strong family and community relationships and ensure good parenting practices, so that both work and family life can be balanced effectively.